BORNEO AND CELEBES IN 19TH CENTURY COLONIAL ERA PORTRAYED BY CONRAD’S AN OUTCAST OF THE ISLAND NOVEL - Nasrullah Nasrullah; M. Natsir; Patrick Tan Jaya (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni dan Budaya, 2021)
Thisstudypretend to describe how Kalimantan and Sulawesi (Celebes) portrayed by Victorian English Author, Joseph Conrad. The researchers use setting theory to identify and analyze the existence of Kalimantan and Sulawesi as setting of place in this Conrad work. Qualitative method and intrinsic element analysis used to collect and analyze the data. The results of this study found that Kalimantan and Sulawesi are exist as setting of place in this work. Therefore, this research conclude that there are the representation of South Asia or Indonesia lands which represented by Victorian English Author, named Joseph Conrad.  Conrad mention Macassar and Pantai as the representation of places in Eastern Coast of Kalimantan and Southern Sulawesi/ Celebes. Otherwise, Conrad also describe a conversation that involved Lingard as a character. Lingard, in the history well known as the Rajah Laut in Eastern Coast of Kalimantan / Borneo in 19th century. This name known as the dominant trader who dominated the trading at that era.